Second chances: men, women and children a decade after divorce - Wallerstein, Judith (1989)
Contents : the nature of divorce,getting in touch : ten years later,winners and losers,heroic efforts and broken hearts,new ties and old ties,danger and opportunity
Includes bibliographical references and index
Keywords: Divorced People